Consumer Acceptance Study Towards Malong (Muarenesox talabon) Fishball with Different Fixative - Suprianto '; Mirna Ilza; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This Research aims to study usage of four as fixative with appropriate concentration, until malong fishball obtain with appearance, aroma, taste and texture which can be accept by consumer. Applied treatment was addition of 25%, 50%, 75% tapioca flour and 25%, 50%, 75% sago flour. Observed parameter was proximate test and organoleptic test tards malong fishball. Research result show that malong fishball with different flour formulate favored by consumer. Malong fishball contains: 39,15 water, 3,16 ash, 29,15 protein, 2,44 fat, 42,03 carbohydrat.Keywords: Fishball, Malong Fish, Flour, Consumer Acceptance